Geology of Eastern Karakoram, Ladakh District, India - Rai, Hakim (Journal of Nepal Geological Society, 1995)
The eastern Karakoram lies to the north of the Shyok ophiolite melange belt (commonly known as the Shyok Suture). Metamorphic rocks are limited in occurrence and mainly confined to the either side of the batholith. Sedimentation history of the Karakoram Basin or the Karakoram Tethys spans from Carboniferous to post-Cretaceous and was confined to the north of the Karakoram Batholith. To the north and east, this basin was not confined to the Karakoram Range but extends beyond its limits. Lower part of the sedimentary sequence is dominated by argillites, siliciclastics and carbonates of Carboniferous to Permian. Basic to intermediate lava flows, sometimes with large pillows, are commonly associated with these sediments particularly in the eastern part of the area. Upper part of the basin, exposed to the north of Chhungtash and extending beyond the Karakoram Pass, is dominated by the carbonates. The end phase of deposition in the Karakoram Tethys is marked by coarse elastic deposits of molassic nature during the post-Cretaceous period. The Karakoram Batholith defines the southern limit of the Karakoram in its eastern part. In the north it intrudes the metamorphics and lower part of the Karakoram Tethys. Along the southern margin the granitoids have intruded the Shyok ophiolitic melange and metasediments. Compositionally, the granitoids of the batholith varies from tonalite to granite which become porphyritic to the south. Magmatic activity within the batholith and also in the Karakoram Tethys ended with the intrusion of a variety of dykes within the batholith. Some of the recent workers working on the Western Karakoram region (from Pakistan side) considered the origin of theKarakoram batholith primarily due to a complex combination of subduction and tectonism. According to them, initially the granitoids were generated by a subduction along the Pamir Suture, subsequently by a subduction along the Shyok Suture and final phase came due to collision. However, present study in the eastern Karakoram points out the emplacement of the batholith along the interface of oceanic and continental margin. The Karakoram batholith is very far from the Pamir Suture. Therefore its origin cannot be related to the subduction along the Pamir Suture. The batholith is very young and has come at the time when Ladakh Batholith was emplaced or at a later date.